Exploring the use of ageing simulation to enable nurses to gain insight into what it is like to be an older person. Issue 23 (23rd September 2020) - Bowden, Alera; Wilson, Valerie; Traynor, Victoria; Chang, Hui‐Chen (Rita)
Abstract: Aim and objectives: To explore the thoughts and experiences of aged care nurses following participation in an ageing‐suit simulation intervention. Background: Globally, people are living longer, and for nurses, there are increasing challenges to meet the needs of the higher numbers of older people in hospital. Educating nurses to understand the ageing process and the experiences of older people in hospital is crucial to addressing these challenges. Ageing‐suits were identified as a possible approach to assist with these educational needs. Design: This study adopted a qualitative descriptive design. Method: A convenience sample of nurses ( n  = 15) were selected from a single aged care ward. Volunteered nurses participated in a four‐hour ageing‐suit simulation session. Their immediate thoughts and experiences were explored via postsimulation debriefs, and three 30‐to 50‐min follow‐up focus groups were conducted at 3 months to explore perceptions on the impact of their experience on clinical practices. The data were analysed with the Braun and Clarke's six‐step thematic analysis method. To ensure quality reporting of this study, the COREQ checklist was utilised (see Appendix S1). Results: Data analysis generated three main themes. Nurses in the study highlighted that the experience of the ageing‐suit resulted in "it feels real" (theme 1) and helped them in "enhancing understanding" (theme 2) about older people and their practices and supported a process of "changing me" (theme 3). Conclusion: Ageing‐suits are emerging as a promising innovative educational approach for aged care nurses to gain insight into the challenges of ageing and subsequently making changes to themselves and their individualised practices towards older people. Future research is required to determine whether this educational approach is useful for a broader population of healthcare professionals. Relevance to clinical practice: Ageing‐suits were identified as a worthwhile educational approach for aged care nurses to improve their specialised clinical practices with older people.